2006
DOI: 10.1534/genetics.105.047209
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Quantitative Trait Loci Across Recombinant Inbred Lines and Testcross Populations for Traits of Agronomic Importance in Rice

Abstract: This study was conducted to determine whether quantitative trait loci (QTL) controlling traits of agronomic importance detected in recombinant inbred lines (RILs) are also expressed in testcross (TC) hybrids of rice. A genetic map was constructed using an RIL population derived from a cross between B5 and Minghui 63, a parent of the most widely grown hybrid rice cultivar in China. Four TC hybrid populations were produced by crossing the RILs with three maintaining lines for the widely used cytoplasmic male-ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
29
4
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 46 publications
10
29
4
4
Order By: Relevance
“…Most of these QTLs appear to coincide with those of loci described in the literature (www.gramene.org). Thus, the chromosome 2 locus qTGW2 (between RM6263 and RM6165) maps to a similar location as does GW2 (Song et al 2007); qTGW6.1 (between RM251 and RM554) is probably the same locus described by Xing et al (2002), Hittalmani et al (2003) and Gao and Zhu (2007); while qTGW11.1 (between RM25948 and RI01970) appears to be the same as the chromosome 11 locus detected by Li et al (2000), Brondani et al (2002) and You et al (2006); qGW5.1 (between RM7373 and RM169) share the same location with qSW5 (Shomura et al 2008) and qGW6.2 (between RM541 and b6-10) is probably the same grain width locus described by Tan et al (2000). However, as qTGW7 has not been previously identified, we chose to detail its map location on the short arm of chromosome 7, and showed that it is co-segregated with RM22034.…”
Section: Cssls Enable the Genetic Analysis Of Complex Traitssupporting
confidence: 64%
“…Most of these QTLs appear to coincide with those of loci described in the literature (www.gramene.org). Thus, the chromosome 2 locus qTGW2 (between RM6263 and RM6165) maps to a similar location as does GW2 (Song et al 2007); qTGW6.1 (between RM251 and RM554) is probably the same locus described by Xing et al (2002), Hittalmani et al (2003) and Gao and Zhu (2007); while qTGW11.1 (between RM25948 and RI01970) appears to be the same as the chromosome 11 locus detected by Li et al (2000), Brondani et al (2002) and You et al (2006); qGW5.1 (between RM7373 and RM169) share the same location with qSW5 (Shomura et al 2008) and qGW6.2 (between RM541 and b6-10) is probably the same grain width locus described by Tan et al (2000). However, as qTGW7 has not been previously identified, we chose to detail its map location on the short arm of chromosome 7, and showed that it is co-segregated with RM22034.…”
Section: Cssls Enable the Genetic Analysis Of Complex Traitssupporting
confidence: 64%
“…It is determined by synthesis and accumulation of starch in grain endosperm (You et al, 2006 andMei et al, 2005). Results revealed that ISR 42-8 yielded less and had lower 100-grain weight than Scarlett under well-watered and drought conditions.…”
Section: -Grain Weight (100-gw)mentioning
confidence: 99%
“…You et al (2006) menyebutkan bahwa sifat dari varietas hibrida ditentukan oleh sifat kedua tetuanya. Jika sifat tetua yang saling mendukung bergabung, akan dihasilkan turunan yang memiliki sifat gabungan yang lebih baik dari kedua tetuanya.…”
Section: Pendahuluanunclassified